Poor menstrual hygiene management – an adverse outcome of menstrual stigmatization in Pakistan - Rabia Maryam Mustafa; Asmat Zehra (Journal of the Pakistan Medical Association, 2021)
Dear Editor, menstrual hygiene management (MHM) is defined as the awareness and confidence to manage one’s periods using hygienic products, having bathing and washing facilities and the ability to dispose of used menstrual products with dignity and privacy [1]. In Pakistan’s predominantly conservative society, menstruation and menstrual practices still face many social, cultural, and religious restrictions. Menstruating women are often considered impure and unclean [2]. As a result, women have to deal with significant challenges in MHM and adverse reproductive health outcomes. Continuous...